Similarity-Based Pattern Recognition First International Workshop, SIMBAD 2011, Venice, Italy, September 28-30, 2011. Proceedings - Pelillo, Marcello; Hancock, Edwin R.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the proceedings of the First International Workshop on Similarity Based Pattern Recognition, SIMBAD 2011, held in Venice, Italy, in September 2011. The 16 full papers and 7 poster papers presented were carefully reviewed and selected from 35 submissions. The contributions are organized in topical sections on dissimilarity characterization and analysis; generative models of similarity data; graph-based and relational models; clustering and dissimilarity data; applications; spectral methods and embedding.
Keywords: Computer science; Computer software; Database management; Artificial intelligence; Computer vision; Optical pattern recognition; Computer Science; Pattern Recognition; Image Processing and Computer Vision; Artificial Intelligence (incl. Robotics).; Database Management; Algorithm Analysis and Problem Complexity; Information Systems Applications (incl. Internet).